Missing Numbers - 5

Logic Level 2

4 , 6 , 16 , 62 , 308 , ? \large 4,6,16,62,308, \boxed{?}

Find what number should replace the square.


Next one : Missing Numbers - 6

Previous one : Missing Numbers - 4

698 990 772 1846

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

X X
Nov 24, 2018

4 × 2 2 = 6 4\times2-2=6 6 × 3 2 = 16 6\times3-2=16 16 × 4 2 = 62 16\times4-2=62 62 × 5 2 = 308 62\times5-2=308 308 × 6 2 = 1846 308\times6-2=1846


Generally, it follows a n = n a n 1 2 a_n=na_{n-1}-2

Henry U
Nov 25, 2018

Explicit formula:

a n = 4 n ! 2 ( 1 + k = 2 n 1 n ! k ! ) , n > 1 a_n = 4 \cdot n! - 2 \left( 1+ \displaystyle \sum_{k=2}^{n-1} \frac {n!}{k!} \right), n > 1

a 6 = 4 6 ! 2 ( 6 ! 2 ! + 6 ! 3 ! + 6 ! 4 ! + 6 ! 5 ! ) = 1846 \Rightarrow a_{\color{#D61F06}6} = 4 \cdot {\color{#D61F06}6}! - 2 \left( \frac{{\color{#D61F06}6}!}{2!} + \frac{{\color{#D61F06}6}!}{3!} + \frac{{\color{#D61F06}6}!}{4!} + \frac{{\color{#D61F06}6}!}{5!}\right) = \boxed{1846}


I found this by multiplying out the terms, but I didn't simplify anything

a 1 = 4 = a a 2 = a 2 2 a 3 = ( a 2 2 ) 3 2 = a 2 3 2 3 a 4 = ( ( a 2 2 ) 3 2 ) 4 2 = a 2 3 4 2 3 4 2 a 5 = ( ( ( a 2 2 ) 3 2 ) 4 2 ) 5 2 = a 2 3 4 5 2 3 4 5 2 5 a 6 = ( ( ( ( a 2 2 ) 3 2 ) 4 2 ) 5 2 ) 6 + 2 = a 2 3 4 5 6 2 3 4 5 6 2 5 6 2 a 7 = ( ( ( ( ( a 2 2 ) 3 2 ) 4 2 ) 5 2 ) 6 2 ) 7 2 = a 2 3 4 5 6 7 2 3 4 5 6 7 2 5 6 7 2 7 2 \begin{aligned} a_1 & = 4 = a \\ a_2 & = a\cdot2-2 \\ a_3 & = (a\cdot2-2)\cdot3-2=a\cdot2\cdot3-2\cdot3 \\ a_4 & = ((a\cdot2-2)\cdot3-2)\cdot4-2=a\cdot2\cdot3\cdot4-2\cdot3\cdot4-2 \\ a_5 & = (((a\cdot2-2)\cdot3-2)\cdot4-2)\cdot5-2=a\cdot2\cdot3\cdot4\cdot5-2\cdot3\cdot4\cdot5-2\cdot5 \\ a_6 & = ((((a\cdot2-2)\cdot3-2)\cdot4-2)\cdot5-2)\cdot6+2=a\cdot2\cdot3\cdot4\cdot5\cdot6-2\cdot3\cdot4\cdot5\cdot6-2\cdot5\cdot6-2\\ a_7 & = (((((a\cdot2-2)\cdot3-2)\cdot4-2)\cdot5-2)\cdot6-2)\cdot7-2=a\cdot2\cdot3\cdot4\cdot5\cdot6\cdot7-2\cdot3\cdot4\cdot5\cdot6\cdot7-2\cdot5\cdot6\cdot7-2\cdot7-2 \\ \vdots & \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...